6(x-4)=-2(x+8

Simple and best practice solution for 6(x-4)=-2(x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-4)=-2(x+8 equation:



6(x-4)=-2(x+8
We move all terms to the left:
6(x-4)-(-2(x+8)=0
We multiply parentheses
6x-(-2(x+8)-24=0

See similar equations:

| 2x=3x-5x+8 | | -2(2x+3)-10=-20 | | ((3x+12)+5=0 | | 4x-4=-16+8x | | 8+4(2+9x)=88 | | 225=5/6p | | 8+4(2+9x=88 | | 8x‐3Y+11=0 | | 62-9x=-5x+78 | | 21-2x=-5x= | | -4(5)+9y=16 | | -(7+6w)=49 | | 4/3v=15 | | -62-9x=-5x=78 | | 1/4e-3/4=1/8 | | h²=121 | | 6x+8=3x-7= | | -8(n+8)=-4(2n+3)=4n | | -5(3x+9=-175 | | 9x-12=-6+8= | | 8(4+11x)=120 | | 62-9x=-5x=78 | | X+85+4x-14=180 | | Y+16-4y=-4 | | 74=2w | | 6x=9x-2x | | 5-2(a+7=32 | | y/2-5=8 | | 2(x+4)=-3(x=5) | | -4x=40+x | | 49w^2+56w+16=0 | | x–4+x–2=180 |

Equations solver categories